Evaluating a standardised tool to explore the nature and extent of foot and ankle injuries in amateur and semi-professional footballers. Issue 1 (March 2015) - Evans, S.; Walker-Bone, K.; Otter, S.
Highlights Most research on foot/ankle injuries among footballers is from professional players. We developed a new questionnaire suitable for use among non-professional players. The questionnaire was acceptable and well-answered by non-professional footballers. These players reported a high number of foot/ankle injuries.